Pengaruh Promosi, Kualitas Pelayanan dan Citra Merek Yamaha Terhadap Keputusan Pembelian Produk Pada PT. Aspacindo Kedaton Motor - Fany Dortua Silalahi; Shofyan Roni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to determine the effect of promotion, service quality, and brand image on product purchasing decisions at PT. Aspacindo Kedaton Motor. The background of this study arose because Yamaha motorcycle sales at the dealership fluctuated every year. This was thought to be caused by less than optimal promotion, inconsistent service, and an insufficiently strong brand image in the minds of consumers. This study used a quantitative method with a sample of 100 respondents determined using the Slovin formula. Data were collected through questionnaires and processed with the help of the SPSS version 25 program using multiple linear regression analysis. The results showed that promotion, service quality, and brand image had a positive and significant effect on purchasing decisions, both partially and simultaneously. The coefficient of determination (R²) value was 0.783, which means that 78.3% of purchasing decisions can be explained by these three variables, while the rest was influenced by other factors outside this study. These results indicate that the better the company's promotion, service, and brand image, the higher the consumer interest in purchasing products at PT. Aspacindo Kedaton Motor.